Internet advertising : a study of the automobile industry in Singapore - Chan, Melissa Ai Leng (2008)
This is an exploratory study of the effectiveness of Internet advertising for automobile industry in Singapore compared with print advertising. A sample of 100 Singaporeans surveyed through e-mail found that Singaporeans relied more heavily on newspapers than the Internet when it came to buying and selling their cars.